2001
DOI: 10.1029/2000jc000361
|View full text |Cite
|
Sign up to set email alerts
|

Variation of sea surface height at periods of 65–220 days in the subtropical gyre of the North Pacific

Abstract: spring and fall conditions. Although Qiu's study sheds light on one possible dynamical process for eddy production in the STCC region, there remain unknown statistical features of the SSH variations. In particular, his study focused on the eddy kinetic energy averaged over the entire STCC region with no discussion on the detailed spatial distribution of the SSH disturbances.The present paper examines statistical properties and detailed spatial distribution of the SSH disturbances in the STCC region using altim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 33 publications
5
44
0
1
Order By: Relevance
“…[4] Analyses of the satellite data have showed that mesoscale eddies with a spatial scale of 500 -800 km and a time scale of 45-180 days are active both south of Japan and east of Taiwan [e.g., Ebuchi and Hanawa, 2000;Kobashi and Kawamura, 2001]. Some observational studies suggested that these mesoscale eddies play important roles in the Kuroshio path variation south of Japan [Book et al, 2002;Ebuchi and Hanawa, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Analyses of the satellite data have showed that mesoscale eddies with a spatial scale of 500 -800 km and a time scale of 45-180 days are active both south of Japan and east of Taiwan [e.g., Ebuchi and Hanawa, 2000;Kobashi and Kawamura, 2001]. Some observational studies suggested that these mesoscale eddies play important roles in the Kuroshio path variation south of Japan [Book et al, 2002;Ebuchi and Hanawa, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…At the zone between 135°and 150°E, a low GM/ JSD zone separates the STF and KF. Its longitudinal range is consistent with the area that has relatively larger mesoscale sea surface height variability (Kobashi and Kawamura 2001). Therefore, our area of interest is the separated STF zone (20°-32°N, 135°-150°E).…”
Section: Sst Front Disappearancementioning
confidence: 92%
“…There are other possible mechanisms. The interaction between mesoscale eddies (Kobashi and Kawamura 2001;Liu and Li 2007) and the mean flow could cause the HLCC to vary. The detailed investigations are needed in future.…”
Section: Linear Rossby Wave Modelmentioning
confidence: 99%